2011
DOI: 10.3748/wjg.v17.i41.4662
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of laparoscopicvsopen gastrectomy in gastric cancer management

Abstract: 17|Issue 41| WJG|www.wjgnet.com related and overall survival probability by Kaplan-Meier method showed comparable results (P = 0.81 and P = 0.83, respectively). We found no differences in surgical complications in the 2 groups. There was no conversion to open surgery in this series. CONCLUSION:LGS is as effective as OGS in the management of advanced gastric cancer. However LGS cannot be recommended routinely over OGS for the treatment of advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…As regards lymphadenctomy, the mean number of retrieved lymph nodes reported by Asian authors after laparoscopic D2 dissection ranges from 23 to 49, 18 whereas it ranges from 15 to 35 in Western observational studies. 5,[7][8][9][29][30][31] Our outcomes, with a mean number of 30.0 examined lymph nodes, are comparable with these previously reported results and, importantly, are in line with Western criteria (number of lymph nodes harvested > 25) regarding adequate D2 dissection and thus surgical quality for advanced gastric cancer. 38 In conclusion, within the limitations of a nonrandomized analysis, our study contributes to the Western experience by demonstrating both the safety and oncologic efficacy of the laparoscopic approach to the resection of gastric adenocarcinoma.…”
Section: Cianchi Et Alsupporting
confidence: 90%
See 1 more Smart Citation
“…As regards lymphadenctomy, the mean number of retrieved lymph nodes reported by Asian authors after laparoscopic D2 dissection ranges from 23 to 49, 18 whereas it ranges from 15 to 35 in Western observational studies. 5,[7][8][9][29][30][31] Our outcomes, with a mean number of 30.0 examined lymph nodes, are comparable with these previously reported results and, importantly, are in line with Western criteria (number of lymph nodes harvested > 25) regarding adequate D2 dissection and thus surgical quality for advanced gastric cancer. 38 In conclusion, within the limitations of a nonrandomized analysis, our study contributes to the Western experience by demonstrating both the safety and oncologic efficacy of the laparoscopic approach to the resection of gastric adenocarcinoma.…”
Section: Cianchi Et Alsupporting
confidence: 90%
“…and only a few studies comparing laparoscopic and open gastrectomies are prospective or randomized. [5][6][7][8] However, all these studies have clearly shown that the laparoscopic approach can actually reduce surgical trauma and improve the patient's quality of life during the postoperative period compared with the open procedure. 9 Some skepticism still remains regarding the oncological efficacy of the laparoscopic treatment of gastric cancer, in particular on the extent of lymphadenectomy.…”
mentioning
confidence: 99%
“…Another important factor was a significantly higher harvest of lymph nodes for patients undergoing open distal gastrectomy. Further retrospective studies from Asia as well as one prospective trial from Italy confirmed the major aspects of these data [26][27][28]. The rate of recurrence or metachronous metastases was similar for both procedures.…”
Section: Treatment Of Gastric Cancersupporting
confidence: 52%
“…A small-scale RCT and several retrospective studies have demonstrated no significant differences in survival rate, recurrence rate and type of recurrence between LAG and COG (12,(24)(25)(26). Furthermore, a retrospective study by multivariate analysis found that depth of invasion and progression of lymph node metastasis were determinants of prognosis, indicating that survival was not an issue of approach, i.e.…”
Section: Evidence Regarding Long-term Survival Outcomesmentioning
confidence: 99%